Petrographic study of gravel used as concrete coarse aggregate in concrete in Patagonia Argentina - Maiza, Pedro (2010)
Gravels that are predominantly volcanic in composition cover a large area in Argentine Patagonia. They are frequently used as concrete aggregates. It is quite common to find pavements that are deteriorated due to the development of the alkali-silica reaction. The main deleterious constituents are volcanic glass and cryptocrystalline silica. This work comprises a study on the main gravel quarries in the Viedma area (province of Río Negro). A petrographic study of the different lithic components was conducted focussing on the identification of the constituents that cause deleterious reactions in concrete, texture types, the presence of volcanic glass, alterations, and microgranular and amorphous cryptocrystalline silica. The materials studied are considered potentially reactive with respect to the alkali-silica reaction from a petrographic point of view.